Mannerheim : president, soldier, spy - Clements, Jonathan, 1971- (Haus Publishing, 2012)
""An exemplary and generously illustrated account; it incorporates new historical material, and he describes the journey as if he had been there.""--The Times Literary Supplement Gustaf Mannerheim was one of the greatest figures of the twentieth century. He spent two years undercover in Asia as a spy, escaped the Bolsheviks in 1917, lead the anti-Russian forces in the civil war and later, during Finland's darkest hour, lead the defense of his country against the impossible odds of the Winter War. Mannerheim is a fascinating appraisal of an adventurer and explorer who would go on to forge a ne.
Keywords: Mannerheim, Carl Gustaf Emil, -- 1867-1951.; Mannerheim, Carl Gustaf Emil, -- 1867-1951; Soldiers -- Finland -- Biography.; Presidents -- Finland -- Biography.; Russo-Japanese War, 1904-1905.; Russo-Finnish War, 1939-1940.; Finland -- History -- 20th century.; Présidents -- Finlande -- Biographies.; Guerre russo-japonaise, 1904-1905.; Guerre soviéto-finlandaise, 1939-1940.; Finlande -- Histoire -- 20e siècle.; HISTORY -- Europe -- Scandinavia.; BIOGRAPHY & AUTOBIOGRAPHY -- General.; Presidents; Soldiers; Finland; 1900-1999; Biographies; History